O santo do purgatório:a transformação mítica do cangaceiro Jararaca em herói - Alves, Késia Cristina França (2006)
This research intends to narrate the journey of a simple man who was turned into a saint by a group of believers in Mossoró, west of Rio Grande do Norte. We recognized in the story of José Leite Santana, the "cangaceiro" Jararacá, an appropriated land to build an investigative approach of how characters as different as bandit and saint can be interconnected. From the believers speech, a narrative was created about these detachments of concepts based on the hero myth that is shown here as a part of men´s dealing with death